Characterization of metal (Ag,Au)/phthalocyanine thin film/semiconductor structures by impedance spectroscopy technique - Oruc, Cigdem; Erkol, Arden; Altindal, Ahmet (ELSEVIER SCIENCE SA, 2017)
The effect of the metal electrodes on the conduction properties of metal free 8,8 '-tetrakis-bis-(2 ',10 ',16 ',24 '-phthalocyaninyl) methylendioxynaphthalene (2HPc) based devices were investigated using impedance spectroscopy and dc technique. From detailed analysis of dc results it was found that for Au/2HPc/p-Si and Ag/2HPc/p-Si structures completely different mechanisms are responsible for charge transport in reverse bias whereas no differences are observed in forward bias conditions. The impedance spectroscopy results analyzed in terms of an electrical equivalent circuit model. Further analysis of the impedance results showed that the dielectric behavior of the structure dominated by grain boundaries at low frequency region while by grains at higher frequencies. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Impedance spectroscopy; Fowler-Nordheim tunelling; Poole-Frenkel emission; Dielectric relaxation; SENSITIZED SOLAR-CELLS; GAS-SENSING PROPERTIES; MECHANISMS; CONDUCTION; CERAMICS; FILMS; OXIDE; Materials Science; Physics